Interannual variability of terrestrial net ecosystem productivity over China: regional contributions and climate attribution. (3rd January 2019) - Zhang, Li; Ren, Xiaoli; Wang, Junbang; He, Honglin; Wang, Shaoqiang; Wang, Miaomiao; Piao, Shilong; Yan, Hao; Ju, Weimin; Gu, Fengxue; Zhou, Lei; Niu, Zhongen; et al.
Abstract: China's terrestrial ecosystems play an important role in the global carbon cycle. Regional contributions to the interannual variation (IAV) of China's terrestrial carbon sink and the attributions to climate variations are not well understood. Here we have investigated how terrestrial ecosystems in the four climate zones with various climate variabilities contribute to the IAV in China's terrestrial net ecosystem productivity (NEP) using modeled carbon fluxes data from six ecosystems models. Model results show that the monsoonal region of China dominates national NEP IAV with a contribution of 86% (69%–96%) on average. Yearly national NEP changes are mostly driven by gross primary productivity IAV and half of the annual variation results from NEP changes in summer. Regional contributions to NEP IAV in China are consistent with their contributions to the magnitude of national NEP. Rainfall variability dominates the NEP annual variability in China. Precipitation in the temperate monsoon climate zone makes the largest contribution (23%) to the IAV of NEP in China because of both the high sensitivity of terrestrial ecosystem carbon uptake to rainfall and the large fluctuation in the precipitation caused by the East Asian summer monsoon anomalies. Our results suggest that NEP IAV can be mainly attributed to ecosystems with larger productivity and response to precipitation, and highlight the importance of monsoon climate systems with high seasonal and interannual variability in driving internannual variation in the land carbon sink.